Experimental infection of cats with Cryptosporidium felis. Issue 10 (October 2022) - Scorza, Andrea V; Tyrrell, Phyllis; Wennogle, Sara; Chandrashekar, Ramaswamy; Lappin, Michael R
Objectives: The aims of this study were to experimentally inoculate cats with Cryptosporidium felis oocysts and compare fecal detection by fluorescent antibody assay (FA) and quantitative PCR (qPCR), and document clinical signs associated with infection. Methods: Cryptosporidium felis oocysts were concentrated from the feces of a naturally infected cat and orally inoculated into six cats that tested negative for C felis by an FA and fecal flotation (FF). Cats were observed daily for the presence of clinical signs consistent with infection. Fecal samples from all cats on days 0 and 9, and one sample per cat (days 18–21), were evaluated by all assays. On day 31, two cats negative for C felis by FF and FA were administered methylprednisolone acetate and all assays were repeated on days 34, 36 and 38. Samples from all cats were tested by FF and FA on days 41, 43, 45 and 48. Results: A total of 41 samples were tested, 25 of which were compared by FA and qPCR. Cryptosporidium felis was detected in 2/25 (8%) and in 19/25 (76%) samples by FA and by qPCR, respectively; the other 16 samples were tested by FF and FA. None of the cats was positive for C felis by FF or FA in samples collected on days 0, 9 or 18–21. One, five and six samples tested positive by qPCR on days 0, 9 and 18–21, respectively. The cats administered methylprednisolone acetate tested positive for C felis by FA on day 36 and by qPCR on days 31, 34, 36 and 38. None of the cats showed clinical signs of disease. Conclusions and relevance: Clinical signs were not recognized in any of the cats for the duration of the study. FA was insensitive compared with qPCR for detecting cats with subclinical C felis infection.